Rodzaje radzenia sobie ze stresem i jakość życia rodzin posiadających dzieci z niepełnosprawnością intelektualną - Roszkowska, Agnieszka (Wydawnictwo Naukowe EDUsfera, 2022)
The appearance of a mentally disabled child in the world shatters the ideals of parents who, before the child’s appearance, already have a certain image of the child and dream of the child developing well, completing school, and finding a good job. When a child with intellectual disabilities arrives, the caregivers are most often unable to imagine how the child will cope in life, and how they themselves will cope with the burden of the child’s illness. Parents must cope with many psychological, but also material, and therapeutic problems related to their child’s disorder, because in addition to the daily activities of caring for the child, for a child with disabilities there are other necessary treatments such as therapy and rehabilitation. An additional burden is the cost of treatment and rehabilitation resulting from the illness of a loved one, which may worsen the financial situation of the family. A single stressor may lead to the emergence of subsequent others, and affect the quality of life of these families.
Keywords: family; intellectual disability; psychological stress; quality of life